Bedside Handover Sebagai Strategi Intervensi Upaya Peningkatan Interaksi Perawat pada Patient-Centered Care - Rahmi Saptarianti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
In health care, the interaction between nurses and patients is essential to build good relationships, increase trust, and meet patient needs and expectations. The success of nursing services depends on the ability of nurses to communicate effectively. One of the causes of unexpected events (KTD) is due to communication errors both verbally and in writing between multidisciplinary and between shifts. Bedside handover can reduce patient safety incidents caused by miscommunication and strengthen employment relations between nurses, thus creating a more collaborative work environment. The purpose of this community service activity in this study is to improve the interaction of nurses when handover to the management of patient-centered care. Data collection techniques are carried out using questionnaires, interviews and direct observations in the treatment room of Karunia Kasih Hospital. In analysing the problems of the data obtained in this study, researchers used Fishbone Analysis which outlined existing problems and analysed using the method of USG (urgency, seriousness, growth) to determine the priority of the problem. The implementation carried out was changing the traditional handover method to bedside handover with the SBAR technique, revising the SOP, conducting socialisation about bedside handover conducting supervision and auditing the implementation of bedside handover. From the data analysis on observations, it can be concluded that bedside handover is an effective strategy to improve interaction between nurses and patients. The results of the analysis of the observation data can conclude that bedside handover is an effective strategy to improve the interaction between nurses and patients in patient-centred care.